Effect of the COVID-19 Pandemic on the Orthopaedic Surgery Residency Application Process: What Can We Learn?. (October 2021) - Wang, Kevin Y.; Babu, Jacob; Zhang, Bo; Jami, Meghana; Musharbash, Farah; LaPorte, Dawn
Abstract : Introduction: The goal of this study was to assess the influence of the coronavirus disease 2019 pandemic on the orthopaedic surgery residency application process in the 2020 to 2021 application cycle. Methods: A survey was administered to the program directors of 152 Accreditation Council for Graduate Medical Education–accredited orthopaedic surgery residency programs. The following questions were assessed: virtual rotations, open houses/meet and greet events, social media, the selection criteria of applicants, the number of applications received by programs, and the number of interviews offered by programs. Results: Seventy-eight (51%) orthopaedic residency programs responded to the survey. Of those, 25 (32%) offered a virtual away rotation, and 57 (75%) held virtual open houses or meet and greet events. Thirteen of these programs (52%) reported virtual rotations as either "extremely important" or "very important." A 355% increase was observed in social media utilization by residency programs between the 2019 to 2020 and 2020 to 2021 application cycles, with more programs finding social media to be "extremely helpful" or "very helpful" for recruiting applicants in 2020 to 2021 compared with the previous year (39% versus 10%, P < 0.001). Conclusion: Although many of the changes seen in the 2020 to 2021 application cycle were implemented by necessity, some of these changes were beneficial and may continue to be used in future application cycles.